2021
DOI: 10.3389/fpsyt.2021.642914
|View full text |Cite
|
Sign up to set email alerts
|

Impulsivity, Social Support and Depression Are Associated With Latent Profiles of Internet Addiction Among Male College Freshmen

Abstract: Background: The rate of internet addiction is increasing in college students. The first year at college is a particularly vulnerable period for internet addiction. Students' psychological characteristics are likely to play an important role in internet addiction. Our study aimed to assess the relationship between impulsivity, social support, depression and internet addiction among male college freshmen.Materials and Methods: The current study utilized latent profile analysis (LPA) to identify at-risk profiles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 82 publications
1
16
0
Order By: Relevance
“…Second, there may exist confounding variables affecting the relationship between depressive symptoms and PIU. Specifically, both perceived social support [47] and sleep quality [74,75] were not measured in our study.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Second, there may exist confounding variables affecting the relationship between depressive symptoms and PIU. Specifically, both perceived social support [47] and sleep quality [74,75] were not measured in our study.…”
Section: Discussionmentioning
confidence: 95%
“…Second, there may exist confounding variables affecting the relationship between depressive symptoms and PIU. Specifically, both perceived social support [ 47 ] and sleep quality [ 74 , 75 ] were not measured in our study. It is possible that individuals that present PIU spend a greater amount of time online, which may impact on their sleep–wake rhythm and, ultimately, contribute to the appearance of depressive symptoms [ 76 , 77 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence revealed that Internet addiction and depression among adolescents is likely to form a vicious circle, that depressed adolescents would have excessive Internet use as a means of alleviating their negative mood, while negative consequences of such excessive use (e.g., social isolation) would further intensify depressive symptoms [ 12 ]. Social support is a basic psychological need that contributes to personal health [ 13 ]. As for Chinese college students, most of them are living independently from their parents for the first time, and their main social environment is composed of peers [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Social support is a basic psychological need that contributes to personal health [ 13 ]. As for Chinese college students, most of them are living independently from their parents for the first time, and their main social environment is composed of peers [ 13 ]. Support from parents and peers appear to be a very important aspect of social support that the students had embraced, and it plays significant roles in students’ socialization, behavioral development, and mental health [ 8 ].…”
Section: Introductionmentioning
confidence: 99%